RESPONSIBILITY OF REGIONAL GOVERNMENT TOWARDS THE IMPLEMENTATION OF AUTONOMOUS EDUCATION ORGANIZATION AND MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION (CASE STUDY OF SERANG CITY) - Suriyanti, Lili; Marpudin, Ade; Aditya, Muhammad (Faculty of Law, Universitas Pekalongan, 2024)
Education policy according to Law Number 20 of 2003 concerning the National Education System is that the state is responsible for the original and absolute responsibility for realizing the ideals of the Indonesian nation. Every citizen has the right to receive education that is in line with human values and justice. Educational problems in Serang City include the many damaged facilities and infrastructure in schools. There were 583 school units that were damaged. However, only 300 classrooms in the seriously damaged category have been proposed, and will be realized in 2024. This article aims to find out the responsibilities of the Serang City Regional Government in Providing Educational Facilities and Infrastructure Based on Law Number 20 of 2003 concerning the National Education System and looking at the inhibiting factors and solution efforts of the Serang City Regional Government in Providing Educational Facilities and Infrastructure in Serang City . The research method used in this research is empirical juridical methods. The regional government of Serang City has a big responsibility in meeting the needs for providing high quality education, including providing adequate facilities and infrastructure. Providing adequate educational facilities and infrastructure is an important component in efforts to improve the quality of education in Serang City. The Responsibility of the Serang City Regional Government in Providing Facilities and Infrastructure. Educational responsibilities based on Law Number 20 of 2003 concerning the National Education System have not yet been fulfilled optimally. The Serang City Government, through the Serang City Education and Culture Office, continues to be committed to advancing the world of education. On the other hand, physical construction of new classrooms (RKB), tables, chairs, teachers' and principals' rooms, library rooms, laboratory rooms, prayer rooms, toilets, sports fields, and roads to schools and New School Units (USB) continues to be pursued. For facilities and infrastructure, the Serang City Education Department continues to take inventory of poor facilities so that they can be built so that the facilities and infrastructure are good and appropriate so that teachers and students who carry out teaching and learning activities are comfortable.